Effect of Different Concentrations of Nano Compounds and Gibberellin in Flower Characteristics of Sweet Pepper Plant ( Capsicum annuum L.) - A. A., Yaseen; M. H., Mejbel (Al-Qadisiyah Journal of Pure Science, 2018)
A pots experiment was conducted in a plantation affiliated to Al-Diwaniya city during the winter season of (2014 - 2015) to find out the effect of different concentrations of Nanoparticles (gold and silver) and gibberellin and their interactions in growth and yield of sweet pepper (C. annuum L.) plant and its contents of mineral, organic and active substance. The design of the experiment was Randomized Complete Blocks (RCBD) in a factorial arrangement (5 Ã— 4), with three replicates, the first factor included five concentrations of Nanoparticles (0Control, 15Au, 30Au, 20Ag and 40Ag) mg. L-1, and the second factor included four concentrations of gibberellin (0, 200, 300 and 400) ml. L-1. Means were compared by using averages revised least significant difference (RLSD) at 0.05 probability level when the treatments referred to significant effect. The results showed: 1- The use of silver nanoparticles by 20 ml. L-1 significant improvements showed in the flowering, fruiting . 2- The use of use gibberellin by 300 mg. L-1 increased the flowering, fruiting and yield characteristics of the pla